The (in)sufficient procedural rights of the victim in criminal proceedings in Bosnia and Herzegovina (not) enable the fight against human trafficking - Associate Professor, Faculty of Law, University of Banja Luka (Glasnik Advokatske komore Vojvodine, 2025)
Human trafficking is a crime against humanity motivated by acquisition of property benefits by torturing the victims.  The victims or injured parties in criminal proceedings in Bosnia and Herzegovina have the right to Claim under Property Law, to be examined as a witness. The injured party is obliged to testify in criminal proceedings and has the right to free legal aid. The position of the victim in criminal proceedings is marginalized because, has no right to appeal against a negative prosecutor's decision, Cessation of Investigation. The subject of plea bargaining also should be confiscation of property gein. Confiscation of property gein is an effective measure in the fight against human trafficking because it can also be applied when there are procedural obstacles to the conduct of criminal proceedings. Confiscation of property gein should not be linked to the initiation of criminal proceedings, because the criminal procedure law does not define when the criminal procedure is considered initiated. The standard of proof for confiscation of gein is an obvious disproportion between assets and incomeis actually accused  can not to prove that he legally acquired the property.
Keywords: Key words: injured party, property claim, human trafficking, confiscation of property.